Hereville : how Mirka got her sword - Deutsch, Barry (Amulet, 2010)
Eleven-year-old Mirka Herschberg dreams of fighting dragons and spends her days honing her skills, even though there are no dragons in her Orthodox Jewish community, but when she accepts a challenge from a mysterious witch, Mirka just might win her dragon-fighting sword after all.